2019
DOI: 10.12737/stp-52201914
|View full text |Cite
|
Sign up to set email alerts
|

Impact of typhoon Vongfong 2014 on the ionosphere and geomagnetic field according to Swarm satellite data: 1. Wave disturbances of ionospheric plasma

Abstract: The article considers the influence of large atmospheric processes on the ionosphere by the example of tropical typhoon Vongfong 2014. We use data obtained from three SWARM satellite missions (450-500 km altitude). We discuss two possible mechanisms of transfer of atmospheric disturbances to ionospheric heights. The first mechanism is the generation of acoustic-gravity waves (AGWs); the second mechanism considers the excitation of electric fields in the atmosphere. We propose new techniques for detecting the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…This lead to a significant difference between ground‐based observations and satellites observations, and the satellites cannot observe the frequencies of AGWs and magnetohydrodynamics (MHD) waves. In addition, some scholars' research on typhoons through SWARM show that typhoon can cause Ne's amplitude changes about 5%–8%, magnetic amplitude changes about 0.5–1.5 nT, and magnetic disturbance frequency is about 0.1–0.5 Hz (Martines‐Bedenko et al., 2019; Zakharov & Sigachev, 2022; Zakharov et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lead to a significant difference between ground‐based observations and satellites observations, and the satellites cannot observe the frequencies of AGWs and magnetohydrodynamics (MHD) waves. In addition, some scholars' research on typhoons through SWARM show that typhoon can cause Ne's amplitude changes about 5%–8%, magnetic amplitude changes about 0.5–1.5 nT, and magnetic disturbance frequency is about 0.1–0.5 Hz (Martines‐Bedenko et al., 2019; Zakharov & Sigachev, 2022; Zakharov et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Its frequency gradually transitions from high frequency to low frequency in the ionosphere. However, Zakharov et al (2019) point out that satellites is much faster than the propagation speed of AGWs, it is impossible for the satellite to observe the changes of AGWs wavelength and other parameters with time in the ionosphere. In addition, since the typhoons studied in this paper are all located on sea and ground-based observation data are few, the wavelength and other physical quantity are not discussed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Zakharov et al. (2019) used Swarm satellite data to study the impact of typhoon 201419 Vongfong on the geomagnetic field and the ionosphere; they showed that the Δ N/N values attained 10% and ∼10‐s period variations in the geomagnetic field reached 0.5–1.5 nT. Yiğit et al.…”
Section: Introductionmentioning
confidence: 99%
“…Isaev et al (2002Isaev et al ( , 2010 and Sorokin et al (2005) estimated the amplitude of the electric fields to be ∼25 mV/m. Zakharov et al (2019) used Swarm satellite data to study the impact of typhoon 201419 Vongfong on the geomagnetic field and the ionosphere; they showed that the ΔN/N values attained 10% and ∼10-s period variations in the geomagnetic field reached 0.5-1.5 nT. Yiğit et al (2016) presented a review of the effects of atmospheric-ionospheric coupling appearing due to various physical causes.…”
mentioning
confidence: 99%